PERAN MODUL PEMBELAJARAN INOVATIF UNTUK MENINGKATKAN PEMAHAMAN BELAJAR MANDIRI SISWA SEKOLAH DASAR - Denia Marsha Khaerunisha; Faza Zakiyyan; Nada Savaira Raihana; Sofyan Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of innovative learning modules in improving the understanding of independent learning of elementary school students. Elementary education is an important phase in building the foundation of students' knowledge, but many students have difficulty understanding the material due to less interesting learning methods. The use of innovative learning modules is one effective solution to overcome this problem. This module is systematically designed to encourage students to learn independently through various media such as digital books, learning videos, and interactive applications. Literature studies are used as a research method to collect data from various library sources related to the concept of innovative learning, learning independence, and the development of learning modules. The results of the analysis show that innovative learning modules play an important role in improving students' understanding through the presentation of more interesting, interactive, and applicable materials. This module also helps students develop critical and creative thinking skills and increases learning independence. However, its implementation in elementary schools still faces challenges such as limited access to technology and teacher readiness in compiling learning modules. Therefore, infrastructure support, teacher training, and module development that are in accordance with student needs are needed to optimize the effectiveness of innovative module-based learning. Keywords: Innovative learning modules, learning independence, elementary schools, interactive learning, literature.